Uji Efektivitas Resin Penukar Ion Amberlite untuk Penurunan TDS, Angka Permanganat, dan Kadar Warna Air Sungai Bengawan Solo: indonesia - Nashira, Alimatun; Anggraeni, Lutvia Yuniar; Muhammad, Nadhev Fadil; Arafahira, Neyza (Teknik Lingkungan Universitas Islam Indonesia, 2025)
Despite often being reported as highly polluted, water from the Bengawan Solo River is widely used for irrigation, farming, industry, sanitation, and even as feedstock for drinking water. To ensure the safety and health of the consument, several parameters for water quality, such as COD, TDS, and color, have been set by the Indonesian government. The quality of the water can be upgraded after a series of treatments, one of which is by ion exchange resin. This research aims to study the effectiveness of Amberlite, one of the most commonly available resins, to treat water from the Bengawan Solo River. The initial river water sample taken in Surakarta shows that it did not qualify for sanitation purposes with TDS 2352 mg/L; color 84 TCU; permanganate number 157,6 mg/L; and pH 5,14. Treatment by cation exchange resin Amberlite HPR 1100 Na decreased the permanganate number, TDS, and color up to 21,02%; 34,01%; and 76,19% respectively, while by anion exchange resin Amberlite HPR 4800 Cl the decreases were up to 10,15%; 32,14% and 86,9%. Using cation exchange followed by anion exchange resin improves the effectiveness slightly, the removal rate of permanganate number, TDS, and color was 25,38%; 38,27%; and 92,86%. Each treatment did not change the pH significantly, while the electrical conductivity change was varied. To get the optimum pollutant removal, the resin had to be treated by HCl 1,5 N for cation resin and by NaOH 1,5 N for anion resin. The results show that Amberlite ion exchange resin was effective only for tertiary water treatment, especially for color removal.